High-dosage carbide slag-based cementitious material: workability, mechanical strength, and carbonation behavior with the performance enhancement - Zheng, Yulong; Liu, Chang; Wang, Jingquan; Pan, Haozhe; Yan, Xingpei; Wagland, Stuart T.; Zhang, Guiyu; Cheng, Liang (Elsevier, 2025)
Cement production generates substantial carbon emissions, necessitating low-carbon alternatives. This study utilized high-dosage carbide slag, a solid waste byproduct of the acetylene industry, to prepare an environmentally friendly and low carbon cementitious materials-CFG (Carbide slag-Fly ash-GGBS system). To investigate the comprehensive performance of CFG, the effects of different dosages of carbide slag (CS, 10%-70%) and silica fume (SF, 0% or 10%), as well as the CO2 capture capacity, were investigated. The environmental assessment was also carried out by using the Life Cycle Assessment (LCA) method. The flexural and compressive strengths of CFG with 10% CS reached 7.7 and 29.2MPa, respectively, at 28 days. It is clear from the micro-analysis that the CS mainly acts as an alkaline stimulant in the cementitious system and can effectively activate FA and GGBS to produce gels. Excessive CS in the system caused Ca(OH)2 accumulation, which negatively affected the system’s strength. This can be remedied by adding SF and carbonization. In particular, after carbonation, the compressive strength of specimens with 30% CS increased by 32.7% from 31.1MPa to 35.7MPa and with 70% CS increase by 80% from 11MPa to 19.8MPa, demonstrating excellent carbon sequestration enhancement properties. The environmental evaluation of the system using LCA shows a substantial suppression of CO2 emissions and energy consumption, with 89.12% and 80.35% reduction, respectively, compared with ordinary Portland cement. Therefore, along with the massive consumption of solid waste, CFG is an environmentally friendly material with the potential to replace conventional cement.
Keywords: 4005 Civil Engineering; 40 Engineering; 12 Responsible Consumption and Production; Carbide slag; Working and mechanical properties; Carbon capture; Hydration mechanism; Solid wastes